Reading an Urban Palimpsest: How the Gradual Loss of an Urban Stream Impacts Urban Form's Connections and Ecosystem Functions - Khirfan, Luna; Mohtat, Niloofar; Daub, Ben (Frontiers in Water, 2021)
Fluvial reclamation to facilitate urban development leads to culverting, hence, a loss of urban streams. Using the palimpsest analogy, we examine how the Amman Stream in Amman (Jordan) historically provided regulatory and socio-cultural ecosystem services through its socio-spatial (longitudinal, lateral, and vertical) connections. We then explore the impact of the stream’s culverting, partially in 1967 then completely in 1997, on these connections and, consequently, on ecosystem services. To overcome data paucity, our methodology relied on constructing spatial data by georeferencing and digitizing aerial photos and satellite images (from 1953, 1975, 1992, and 2000) using ArcGIS. We augmented our data with archival research (historic and contemporary documents and maps), an online survey among Amman’s residents, and in situ observations and photography. The results reveal striking contrasts between the historic and contemporary configuration of urban form vis-à-vis the Amman Stream. Throughout its early urban history during the Classical and early Islamic periods, the urban form elements reflected reverence and prudence towards the Amman Stream as manifested in the investment in water infrastructure and the alignment of thoroughfares, civic monuments, and bridges that collectively capitalized on the land relief (the strath) and established strong connections with the Amman Stream, maximizing, in the process, its regulatory and socio-cultural services. In contrast, the contemporary urban form replaced the stream with car-oriented roads, hence, eradicated its regulatory services and replaced its socio-spatial connections with urban socio-economic and cultural fissures. Accordingly, we propose to daylight (deculvert) the Amman Stream to restore its regulatory and socio-cultural services and its socio-spatial connections. We substantiate the feasibility of daylighting through: 1) morphological analysis that reveals that roads cover most of the stream; 2) the survey’s findings that indicate public support; and 3) the cascading benefits for the larger watershed in a water insecure region.